Relationship of special and functional preparedness of freestyle wrestlers at different stages of sports training - Leonid Volkov; Stepan Zakharkiv (Kharkiv State Academy of Physical Culture, 2019)
The presented experimental data indicate that at all stages of the long-term training of freestyle wrestlers between the ages of 11-12 years old and 17-18 years old there are reliable relationships between the indicators of special and functional readiness. The greatest number of reliable relationships have tests on special preparedness - "rushing on the wrestler's bridge in 1 minute", "coups on the wrestler's bridge in 1 minute". The conducted studies confirm the reliably high interconnection of the components of special and functional preparedness when training adolescents and young men in wrestling. Separate components of these types of training change the information content depending on the stages of preparation, require changes in the total and selective amounts of training loads. Purpose: explore the relationship of the main components of the special and functional preparedness of adolescents and young men engaged in freestyle wrestling at different stages of many years of sports training. Material & Methods: the study is organized on the basis of the Olympic College of Ivan Poddubny with the participation of 90 athletes aged 11 to 18 years. In the course of the experiment, the following methods were used: theoretical analysis, synthesis of practical experience, pedagogical testing, pulsometry, reflexometry, heat measurement, mathematical statistics, correlation analysis. Results: the interrelation of special and functional preparedness of freestyle wrestlers from 11 to 18 years old, studying at different stages of sports training, is established. Conclusions: the study of the problem of the relationship of special and functional preparedness of freestyle wrestlers requires the development of an integrated methodology using the idea of a systems approach. At all stages of athletic training for teenagers and young men aged 11-12 years old to 17-18 years old engaged in freestyle wrestling, there are reliable relationships between the components of special and functional preparedness. According to the informativeness of these indicators vary from the stage of preparation, it requires changes in the volume of training loads of selective and general orientation.